Differential activation of temporal cortex during sentence completion in schizophrenic patients with and without formal thought disorder. - Kircher, T; Bulimore, E; Brammer, M; Williams, S; Broome, MR; Murray, R; McGuire, P (2001)
The neural correlates of processing linguistic context in schizophrenic patients with formal thought disorder (FTD) were examined. Six right-handed male patients with prominent 'positive' FTD were compared with six schizophrenic patients without FTD and seven volunteers, matched for cognitive and demographic variables. Functional magnetic resonance imaging (IMRI) was used to measure cerebral activation while subjects read and completed sentence stems out loud. During a GENERATION condition, subjects were required to generate a word which completed the sentence stem appropriately. During a DECISION condition, subjects selected and articulated one of two presented terminal words. A READING condition served as baseline. The three conditions were compared with each other. Regions activated were identified in each group, and between-group differences were detected using an ANCOVA. When GENERATION was compared with READING, FTD patients showed less activation in the right superior temporal gyrus than patients without FTD or controls, but greater activation in the left inferior frontal, inferior temporal and fusiform gyri. FTD patients also showed an attenuated right temporal response when GENERATION was compared with DECISION. This differential engagement of the right temporal cortex was independent of differences in the speed or accuracy of responses, whereas the left fronto-temporal differences in activation were not evident after covarying for task errors. The attenuated engagement of right temporal cortex, which is implicated in language comprehension at the discourse level, is consistent with neuropsychological evidence linking thought disorder with deficits in processing linguistic context.